2020
DOI: 10.1136/gpsych-2019-100095
|View full text |Cite
|
Sign up to set email alerts
|

Rare case report of Van Gogh syndrome in a patient with paranoid schizophrenia

Abstract: Self-mutilation is often associated with psychiatric disorders. We describe here a 22-year-old male Indian with decreased sleep, aggressive behaviour, self-muttering, disorganised behaviour, frequent spitting, biting and self-mutilation; he bit off his right ring finger and left thumb (Van Gogh syndrome). Self-harm behaviour was frequently evidenced by family members resulting in various injuries. The patient was diagnosed with paranoid schizophrenia and was treated with anti-psychotics which resulted in a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In the context of psychiatric illness, NSSM is further divided into major and minor (or superficial) acts of self-mutilation. Minor acts of self-mutilation are more common and include nail-biting, hair-pulling, and skin-cutting [ 3 , 4 ]. In contrast, major acts of self-mutilation are more often sporadic and result in permanent organ damage [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of psychiatric illness, NSSM is further divided into major and minor (or superficial) acts of self-mutilation. Minor acts of self-mutilation are more common and include nail-biting, hair-pulling, and skin-cutting [ 3 , 4 ]. In contrast, major acts of self-mutilation are more often sporadic and result in permanent organ damage [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 This view, which is propagated by society as well as families, tends to create dislike, discrimination and abandonment towards older people who are living with disability and dementia; it also causes very poor self-worth among them. 8 …”
mentioning
confidence: 99%
“…7 This view, which is propagated by society as well as families, tends to create dislike, discrimination and abandonment towards older people who are living with disability and dementia; it also causes very poor self-worth among them. 8 The opening of the 'Unforgettable Restaurant' is a pioneering initiative. Currently, nearly 10 older people living with disability and dementia are working in this restaurant, and they remain mainly in charge of ordering and serving.…”
mentioning
confidence: 99%
“…Mudgal et al provided us with an interesting and comprehensive case report. 1 The subject of their report presents with typical features of schizophrenia, evidenced by his score on the BPRS (Brief Psychosis Rating Scale). The only atypical features are an age of onset which is slightly younger than average, but this could be explained by his use of cannabis (an estimate of usage would be helpful).…”
mentioning
confidence: 99%
“…Mudgal et al , however, follow the psychiatric literature in reserving ‘Van Gogh syndrome’ for severe self-harm (usually mutilation) associated with psychosis: a review of the literature found five papers (including Mudgal et al ’s), describing six patients with self-mutilation. All were diagnosed with psychosis: one with psychosis unspecified, 2 three with schizophrenia 1 3 4 and two with bipolar disorder. 5 In common usage, therefore, Van Gogh syndrome does not equate to NSSI.…”
mentioning
confidence: 99%